Showing some class [educational assistance]. - Jones, W.D (IEEE spectrum)
This paper presents some important information that relate to the schools around the area was directly hit by typhoon Katrina. The paper provides data on the schools that were hardest hit, the schools that offered to take in displaced students, and the costs repair and reconstruction. It also discusses the plight of an estimated 4500 international students who fled the Gulf Coast to avoid Katrina, and those students currently enrolled at Tulane and Dillard.